Gregory Crewdson - eveningside - Vergne, Jean-Charles 1972- (Edizioni Gallerie d'Italia/Skira, 2022)
Over the past three decades, Gregory Crewdson has been fleshing out a portrait of middle America, an America gazing wide-eyed at the glimmers of a fading dream. His cinematographically staged photos have pieced together the fragments of a twilight world tinged with numbness. This book brings together three bodies of work made between 2012 and 2022. Envisaged as a trilogy, they previde unique insight into a decade of creation and offer a comprehensive view of the universe that has posited Gregory Crewdson as one of the major figures of photography. This trilogy is introduced by Fireflies, a pivotal series if one is to grasp the intimate undercurrents in Gregory Crewdson's artwork
Impressum: "Gregory Crewdson. Eveningside", Gallerie d'Italia - Torino, 12 ottobre 2022 - 22 gennaio 2023
Keywords: Crewdson, Gregory -- 1962-; Ausstellungskatalog -- Gallerie d'Italia -- 12.10.2022-22.01.2023 -- Turin